Preventive effects of the Rehmannia glutinosa Libosch and Cornus officinalis Sieb herb couple on chronic kidney disease rats via modulating the intestinal microbiota and enhancing the intestinal barrier - Wang, Ling; Zhu, Jin-Hui; Jiang, Xiao-Dan; Ma, Zhen-Xiang; Tao, Jin-Hua (Frontiers in Pharmacology, 2022)
CKD is a clinical syndrome with slow development and gradual deterioration of renal function. At present, modern medicine still lacks an ideal treatment method for this disease, while TCM has accumulated rich clinical experience in the treatment of CKD, which can effectively improve renal function and delay renal failure, and has unique advantages. RC is widely used in clinical practice to treat CKD, especially the “Kidney-Yin” deficiency syndrome. However, the compatibility mechanisms responsible for its effects in experimental studies, including preclinical and clinical research studies, are still not fully understood. Adenine-induced CKD rats were used to investigate the preventive effect of RC on CKD rats. Based on the high-throughput 16S rRNA gene sequencing results from Illumina, we discussed the intestinal flora abundance in rats in different treatment groups. According to a PCA and a PCoA based on a distance matrix, there was a clear separation of gut microbiome profiles between normal rats and model rats in terms of beta diversity. The abundance of Firmicutes in CKD rats was relatively increased, while that of Bacteroidetes was decreased. It is clear that the plot for the RC group was closer to that of the normal group, suggesting that the RC group had higher similarities among bacterial members with N rats. Ussing chamber, Western blot, and PCR assays were used to investigate the effects of RC on intestinal barrier function and its molecular mechanism in model animals. The results indicated that the protein expressions of ZO-1, claudin-1, and occludin-1 were decreased significantly in chronic kidney disease rats with the induction of adenine. With the treatment of RG, CO, and RC, the intestinal barrier was repaired due to the upregulated expressions of the aforementioned proteins in CKD rats. Based on our findings, RC appears to strengthen the intestinal barrier and modulate gut microbiota in adenine-induced CKD rats. This project revealed the compatibility mechanism of RC in regulating the intestinal microecology and barrier function to intervene in CKD and provided the basis and ideas for the clinical application of RC and the development of innovative drugs for CKD.